If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 4 = 69 + 6x Reorder the terms: 4 + -7x = 69 + 6x Solving 4 + -7x = 69 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 4 + -7x + -6x = 69 + 6x + -6x Combine like terms: -7x + -6x = -13x 4 + -13x = 69 + 6x + -6x Combine like terms: 6x + -6x = 0 4 + -13x = 69 + 0 4 + -13x = 69 Add '-4' to each side of the equation. 4 + -4 + -13x = 69 + -4 Combine like terms: 4 + -4 = 0 0 + -13x = 69 + -4 -13x = 69 + -4 Combine like terms: 69 + -4 = 65 -13x = 65 Divide each side by '-13'. x = -5 Simplifying x = -5
| -6(4-t)=12t | | 8v+8-2(-6v-1)=2(v-1) | | -3(7x+2)=-5(9-x)-8x | | x^4+8x^3+7x^2+8x+7=0 | | 8x-16=32 | | 5w+9.9=4.8+8w | | x=-4 | | 2(-6a+3)=-(-10+2a) | | 7+3x=-8 | | 95x=143 | | 30=4+4x+2 | | -1-7v=-(3v-3) | | 9=4x-7 | | (4x+5)-3x=11x | | 1k+9=6(k-11) | | -3p-(p+5)=-p-2 | | 3+5x=-x-33 | | 3x^2+24x=27 | | -(-3k+1)+6=3-k | | -2(18-3k)=7k+2k | | -2(x+1)+9x=54 | | -8=2x+4 | | -3=-4(3+5a)+7a | | 6+4(x+8)=-8x+5+x | | -6(-x+1)=-6(3-2x) | | -x^2(x-1)(x+4)=y | | 10x+5+30=100 | | 11(2x+5)=8x+20 | | (3y-4y+5)(y-3y+3)= | | 5x+2+10=3 | | 3n-4=n | | -x^2(x-1)(x+4)=0 |